Egalitarian Attitudes, Gender Roles, and College Students' Beliefs About Dating Behaviors - Zastrow, Karissa (My University, 2011)
The purpose of this study is to investigate how participants' gender and degree of egalitarianism are related to their perceptions of date success when a date involves people engaging in traditionally masculine/feminine behaviors vs. gender neutral behaviors, as well as when the date involves a gain frame vs. loss prevention.
Color poster with text and graphs.
Keywords: Social values--Philosophy; Sex role--Social aspects; College Students--Attitudes; Dating (Social customs)--United States; Posters